Effect of Assemblr Edu on fifth graders’ learning outcomes in the respiratory system - Fira Sekarani; Kusmajid Abdullah (Inovasi Kurikulum, 2025)
The background of this study is based on the low learning outcomes of students, which are attributed to the abstract nature of the material and the lack of engaging visual media. Advances in digital technology offer new opportunities in the learning process, including the use of interactive Augmented Reality (AR) media. This study aims to investigate the effect of Assemblr Edu media on science learning outcomes, specifically on the topic of the human respiratory system. The study employed a quantitative approach with a quasi-experimental method using a non-equivalent control group design. The subjects were fifth-grade elementary school students divided into an experimental class and a control class. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, and an Independent Samples T-Test. The results showed a significant effect of Assemblr Edu media on students’ science learning outcomes. The three-dimensional visualization provided by Assemblr Edu clarified abstract concepts, encouraged active student engagement, and created a more interactive and meaningful learning experience. Thus, the use of Assemblr Edu media is proven to be effective in improving science learning outcomes on the topic of the human respiratory system.   Abstrak Latar belakang penelitian ini didasarkan pada rendahnya hasil belajar peserta didik yang disebabkan oleh kualitas materi yang bersifat abstrak dan kurangnya media visual yang menarik. Kemajuan teknologi digital membuka peluang baru dalam proses pembelajaran, termasuk penggunaan media Augmented Reality (AR) yang interaktif. Penelitian ini bertujuan untuk mengetahui pengaruh media Assemblr Edu terhadap hasil belajar IPAS pada materi sistem pernapasan manusia. Penelitian ini menggunakan pendekatan kuantitatif dengan metode eksperimen semu dan desain non-equivalent control group design. Subjek penelitian adalah peserta didik kelas V SD yang terbagi menjadi kelas eksperimen dan kelas kontrol. Pengumpulan data dilakukan melalui pretest dan posttest, dengan analisis data menggunakan uji normalitas, homogenitas, dan uji Independent Samples T-Test. Hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan penggunaan media Assemblr Edu terhadap hasil belajar IPAS peserta didik. Visualisasi tiga dimensi yang disediakan oleh Assemblr Edu mampu memperjelas konsep abstrak, mendorong keterlibatan aktif peserta didik, serta menciptakan pengalaman belajar yang lebih interaktif dan bermakna. Dengan demikian, penggunaan media Assemblr Edu terbukti efektif dalam meningkatkan hasil belajar IPAS pada materi sistem pernapasan manusia. Kata Kunci: Assemblr Edu; hasil belajar; IPAS; sistem pernapasan; teknologi pendidikan